1-Dimensional Model of Seismic Velocity after Tarutung Earthquake 1 October 2022 Mw 5.8 - Resa Idha; Endah P. Sari; Yusran Asnawi; Andrean V.H Simanjuntak; Syahrul Humaidi; Umar Muksin (Politeknik Negeri Batam, 2023)
On October 1, 2022, an earthquake with a magnitude (M) of 5.8 occurred in the Tarutung region, Indonesia and was associated with an active fault at a depth of 10 km. The earthquake fault with dextral mechanism is suitable with the pattern of active fault movement in Sumatra in the Northeast - Southwest direction. A total of 170 aftershocks occurred within a week span with magnitude variations of 1.7 – 4.0. In addition, the Tarutung earthquake was felt by the local peoples with an intensity of IV - VI MMI and caused 1 fatality, 25 injuries, and around 900 houses were damaged. Therefore, this study studies the characteristics of seismicity and damage caused by finding an appropriate 1-Dimensional seismic velocity model. The obtained 1-Dimensional speed model has varying values at a depth of 10 km with a speed of 5.5 km/s and 30 km with a speed of 7 km/s. The 1-D velocity model obtained has a convergent and unique solution with an RMS value < 1.0. Based on ground motion analysis after relocation, it was found that the high PGA and PGV values were in Tarutung. The PGA results reveal a high percentage value of >10% in Tarutung. This is consistent with the damage data and at the same time confirms that Tarutung is in a seismically active area.